Beyond the VSG layer: Exploring the role of intrinsic disorder in the invariant surface glycoproteins of African trypanosomes - Sülzen, Hagen; Volkov, Alexander N; Geens, Rob; Zahedifard, Farnaz; Stijlemans, Benoit; Zoltner, Martin; Magez, Stefan; Sterckx, Yann G-J; Zoll, Sebastian (PLoS pathogens, 2024)
In the bloodstream of mammalian hosts, African trypanosomes face the challenge of protecting their invariant surface receptors from immune detection. This crucial role is fulfilled by a dense, glycosylated protein layer composed of variant surface glycoproteins (VSGs), which undergo antigenic variation and provide a physical barrier that shields the underlying invariant surface glycoproteins (ISGs). The protective shield's limited permeability comes at the cost of restricted access to the extracellular host environment, raising questions regarding the specific function of the ISG repertoire. In this study, we employ an integrative structural biology approach to show that intrinsically disordered membrane-proximal regions are a common feature of members of the ISG super-family, conferring the ability to switch between compact and elongated conformers. While the folded, membrane-distal ectodomain is buried within the VSG layer for compact conformers, their elongated counterparts would enable the extension beyond it. This dynamic behavior enables ISGs to maintain a low immunogenic footprint while still allowing them to engage with the host environment when necessary. Our findings add further evidence to a dynamic molecular organization of trypanosome surface antigens wherein intrinsic disorder underpins the characteristics of a highly flexible ISG proteome to circumvent the constraints imposed by the VSG coat.
Keywords: Membrane Glycoproteins; membránové glykoproteiny; Variant Surface Glycoproteins, Trypanosoma; trypanosomové variantní povrchové glykoproteiny; Animals; Humans; Trypanosomiasis, African; lidé; trypanozomóza africká; protozoální proteiny; Protozoan Proteins; zvířata